(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
"Ectopia" (less commonly known as "pseudoerosion") is a modern term that refers to the protrusion of the mucous membrane outside the cervical canal. Ectopia is often called erosion, which is not entirely correct. In this article, we will explain how ectopia differs from erosion and which of these conditions should be treated.